Accidental Overdose of Paliperidone Palmitate. (11th April 2019) - Ojimba, Chiedozie; Oyelakin, Ayotomide; Khandaker, Taher
Abstract : Long-acting injectable (LAI) antipsychotics first introduced in 1960s are useful in the treatment of schizophrenic patients with poor medication adherence due to their maintaining feature of therapeutic plasma level without daily administration. Paliperidone Palmitate is one of such LAI antipsychotic drugs used due to its benefit of maintaining a therapeutic plasma level with four-week interval of injections. We report the case of a 21-year-old male with a history of mental illness that presented with selective mutism, disorganized speech, thought process and behavior, and auditory hallucinations who accidentally received 624 mg Paliperidone Palmitate intramuscularly with no reported side effects after 2 weeks of monitoring and observation. Paliperidone is a D2, 5HT2A receptor antagonist with additional antagonist activity at α -1 and α -2, H-1 receptor sites, and four metabolic pathways identified for its metabolism. Studies have reported adverse effects such as acute dystonia, acute renal failure, and cardiovascular abnormalities with Paliperidone overdose; however there is no reported literature on Paliperidone Palmitate overdose, though there have been reported cases of Paliperidone Palmitate side effects of hypersexuality and angioedema with the standard dose.